A Survey of Production Systems, Management and Marketing Strategies for Tswana Goats in Semiarid Areas around Mafikeng, North West Province. (1st November 2016) - Tsheole, M.S.; Mlambo, V.; Mwanza, M.
Abstract: Goat production in communal areas is faced with numerous challenges which may differ with geographical locations. Marketing of goats in North West province has a potential to help diversify the economy and alleviate poverty in rural communities. Seventy five farmers from three villages were randomly interviewed on the management and marketing of goats. Results showed that 57 percent of farmers sold animals without weighing and were also affected by weak market value of livestock. About 29 percent of farmers mentioned that they encountered abortion due to droughts, mineral deficiencies. Other factors include poor housing, low soil fertility for forage production contributed to poor productivity. In addition major constrain for goat production were stock theft (45%), malnutrition (33%) and diseases (32%). A significant correlation (P<0.005) was observed between grazing system and access to veterinary (P<0.005). There is a need to educate rural farmers on management and marketing of goat. This will make significant contribution in addressing the problem of goat management.